Effects of a health education program on cytokines and cortisol levels in fibromyalgia patients: a randomized controlled trial - Andrei Pereira Pernambuco; Lucina de Souza Cota Carvalho; Luana Pereira Leite Schetino; Janaíne Cunha Polese; Renato de Souza Viana; Débora d’ Ávila Reis (Advances in Rheumatology, 2018)
Abstract Background Fibromyalgia (FM) is a syndrome characterized by widespread chronic pain associated to other symptoms, such as: fatigue, anxiety, depression and sleep disorders. Health education programs (HEP) have emerged as good non-pharmacological strategies to treat it. However, it is still not clear if the benefits are only subjective, or it has also objective impacts on immune and or neuroendocrine systems. Methods Fifty-eight fibromyalgia women were randomly allocated in experimental group (n = 27) or control group (n = 31). The experimental group was submitted to HEP treatment for 11 weeks, while control group did not receive intervention at the same period. All data were collected at zero and 11th week by a blinded researcher. The statistical analysis were made in GraphPad Prism software (version 5.0) with significant level adjusted for α = 0.05. Results Forty-four patients concluded the full study, 21 in the experimental group and 23 in the control group. Intragroup and intergroup analysis revealed that treatment induced significant increases of IL-4 plasma levels, anti-inflammatory cytokine/inflammatory cytokine ratio (AC/IC ratio), salivary cortisol levels, in addition to significant decreases on FIQ scores. Intergroup variation analyses revealed also significant increases of IL-10 plasma levels. Conclusion The results presented suggest that this kind of HEP could induce subjective and objective changes (immune and neuroendocrine), that could explain, at least in part the improvement of fibromyalgia patient’s health status. (Clinical Trial Registration Number - ReBEC - RBR-5tdnbr).